Educational technology for breast self-examination in blind women - Lorita Marlena Freitag Pagliuca; Eugênia Maria Costa (Rev Rene)
This is a study aimed at the development of educational materials and at the design of a health education method for blind women under breast cancer prevention. A chart on the anatomy of the breast, a 3D prototype of the breast and an explicative CD describing what cancer is, what its risk factors are and how to prevent it by performing self-examination were developed. Four blind women comprised the sample. Instruction was evaluated before the use of the material. The teaching method associated the self-instructional material with the nursing appointment. The evaluation confirmed that the employment of hearing and touch facilitate learning, in which stands out the clarity of oral language and, in what concerns the prototype and the chart, they have facilitated the perception of the content.